Warming up before a 20-minute endurance effort: Is it really worth it? - Barranco-Gil, D.; Alejo, L. B.; Valenzuela, P. L.; Gil-Cabrera, J.; Montalvo-Pérez, A.; Talavera, E.; Moral-González, S.; Clemente-Suárez, V. J.; Lucia, A. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To analyze the effects of different warm-up protocols on endurance-cycling performance from an integrative perspective (by assessing perceptual, neuromuscular, physiological, and metabolic variables). Methods: Following a randomized crossover design, 15 male cyclists (35 [9] y; peak oxygen uptake [VO2peak] 66.4 [6.8] mL/kg·min) performed a 20-minute cycling time trial (TT) preceded by no warm-up, a standard warm-up (10 min at 60% of VO2peak), or a warm-up that was intended to induce potentiation postactivation (PAP warm-up; 5 min at 60% of VO2peak followed by three 10-s all-out sprints). Study outcomes were jumping ability and heart-rate variability (both assessed at baseline and before the TT), TT performance (mean power output), and perceptual (rating of perceived exertion) and physiological (oxygen uptake, muscle oxygenation, heart-rate variability, blood lactate, and thigh skin temperature) responses during and after the TT. Results: Both standard and PAP warm-up (9.7% [4.7%] and 12.9% [6.5%], respectively, P<.001), but not no warm-up (?0.9% [4.8%], P=.074), increased jumping ability and decreased heart-rate variability (7.9% [14.2%], P=.027; 20.3% [24.7%], P=.006; and 1.7% [10.5%], P=.366). Participants started the TT (minutes 0-3) at a higher power output and oxygen uptake after PAP warm-up compared with the other 2 protocols (P<.05), but no between-conditions differences were found overall for the remainder of outcomes (P>.05). Conclusions: Compared with no warm-up, warming up enhanced jumping performance and sympathetic modulation before the TT, and the inclusion of brief sprints resulted in a higher initial power output during the TT. However, no warm-up benefits were found for overall TT performance or for perceptual or physiological responses during the TT.